Ictal EEG source imaging and connectivity to localize the seizure onset zone in extratemporal lobe epilepsy. (May 2020) - Vespa, Simone; Baroumand, Amir G.; Ferrao Santos, Susana; Vrielynck, Pascal; de Tourtchaninoff, Marianne; Feys, Odile; Strobbe, Gregor; Raftopoulos, Christian; van Mierlo, Pieter; El Tahry, Riëm
Highlights: An automated algorithm was implemented for ictal ESI and subsequent connectivity from low-density EEG. Connectivity analysis may improve the localization of the seizure onset zone in extratemporal lobe epilepsy. Good localization was obtained also from diffuse hemispheric or bilateral ictal patterns. Abstract: Purpose: To evaluate the yield of Functional Connectivity (FC) in addition to low-density ictal Electrical Source Imaging (ESI) in extratemporal lobe epilepsy (ETLE), using an automated algorithm for analysis. Method: Long-term EEG monitoring of consecutive ETLE patients who underwent surgery was reviewed by epileptologists, and seizure onsets characterized by rhythmical activity were identified. A spectrogram-based algorithm was developed to select objectively the parameters of ESI analysis. Two methods for SOZ localization were compared: i) ESI power, based on LORETA exclusively; ii) ESI + FC, including a Granger causality-based connectivity analysis. Results were determined at a sublobar level. The resection zone, in relation to 1-year follow-up surgical outcome, was considered as reference standard for diagnostic accuracy analyses. Results: Ninety-four seizures from 24 patients were analyzed. At seizure-level, ESI power showed 36 % sensitivity and 72 % specificity (accuracy: 45 %). ESI + FC significantly improved the accuracy, with 52 % sensitivity and 84 % specificity (accuracy: 61 %, p = 0.04). Results of ESI + FC were equally valuable in patients with lateralized or bilateral/generalized visual interpretation of ictal EEG. In a patient level sub-analysis, upon blinded clinical interpretation, ESI + FC showed a correct localization in 67 % of patients and substantial inter-rater agreement (kappa = 0.64), against 27 % achieved by ESI power, with fair inter-rater agreement (kappa = 0.37). Conclusion: FC significantly improves SOZ localization compared to ESI solely in ETLE. Ictal ESI + FC could represent a novel option in the armamentarium of presurgical evaluation, aiding also in patients with visually non-localizable scalp ictal EEG. Prospective studies evaluating the clinical added value of automated low-density ictal ESI may be justified.